On the error probability of linearly modulated signals on frequency-flat Ricean, Rayleigh, and AWGN channels - Shayesteh, M.G.; Aghamohammadi, A. (IEEE transactions on communications, 1995)
The method used in Aghamohammadi and Meyr (1990) for finding the error probability of linearly modulated signals on Rayleigh frequency-flat fading channels has been applied to the more general case of Ricean fading. A signal received on a fading channel is subject to a multiplicative distortion (MD) and to the usual additive noise. Following a compensation of the MD, the signal provided to the detector may be thought to include only a single additive distortion term ("final noise"), which comprises the effects of the original additive noise, the MD, and the error in MD compensation. An exact expression for the probability density function of the final noise is derived. This allows calculation of error probability for arbitrary types of linear modulations. Results for many cases of interest are presented. Furthermore, as special cases of Ricean fading, error probability for Rayleigh fading and non-fading channels are obtained which either match the results or complete the approximate derivations formerly known from the literature.< >